Cancer in Organ Transplant Recipients - Schmähl, Dietrich; Penn, Israel (Springer Berlin Heidelberg, 1991)
In about 5% of all organ (kidney, liver) transplant recipients, malignancies occur as a late complication of the massive immunosuppression. The malignancies are mainly skin cancers, lymphomas and renal carcinomas. The present book discusses the possible mechanisms of this type of tumorigenesis and inquires into possibilities of prevention. In particular, the described malignancies might be of viral origin. The book informs about a completely new type of carcinogenesis. Apart from the scientific aspects, it is of great practical value
Keywords: Oncology; Surgery; Hepatology; Gastroenterology; Virology; Allergology; Oncology; Clinical medicine; Medical virology; Allergy; Transplantation; Immunsuppression; Krebs -- Medizin; Spätkomplikation; Konferenzschrift -- 1990 -- Heidelberg